Mineral substrate quality determines the initial soil microbial development in front of the Nordenskiöldbreen, Svalbard - Luláková, Petra; Šantrůčková, Hana; Elster, Josef; Hanáček, Martin; Kotas, Petr; Meador, Travis; Tejnecký, Václav; Bárta, Jiří (FEMS microbiology ecology, 2023)
Substrate geochemistry is an important factor influencing early microbial development after glacial retreat on nutrient-poor geological substrates in the High Arctic. It is often difficult to separate substrate influence from climate because study locations are distant. Our study in the retreating Nordenskiöldbreen (Svalbard) is one of the few to investigate biogeochemical and microbial succession in two adjacent forefields, which share the same climatic conditions but differ in their underlying geology. The northern silicate forefield evolved in a classical chronosequence, where most geochemical and microbial parameters increased gradually with time. In contrast, the southern carbonate forefield exhibited high levels of nutrients and microbial biomass at the youngest sites, followed by a significant decline and then a gradual increase, which caused a rearrangement in the species and functional composition of the bacterial and fungal communities. This shuffling in the early stages of succession suggests that high nutrient availability in the bedrock could have accelerated early soil succession after deglaciation and thereby promoted more rapid stabilization of the soil and production of higher quality organic matter. Most chemical parameters and bacterial taxa converged with time, while fungi showed no clear pattern.
Keywords: glacier forefield; Ice Cover; microbial assembly; Minerals; Arctic soils; Bacteria; půda; Soil; deglaciation; ledový příkrov; minerály; biogeochemistry; soil succession; půdní mikrobiologie; Soil Microbiology; Svalbard